Opportunities and Challenges of Implementing the Minister of Foreign Affairs Regulation in the Practice of Buying and Selling Used Clothes - Kawakib Kawakib; Q. Zaman (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
Although there is a ban on the import of used clothing as stipulated in the Regulation of the Minister of Trade Number 51/M-DAG/PER/7/2015. However, the practice of buying and selling imported used clothing in Central Market, Pontianak City is still quite rampant. This study aims to analyze the opportunities and challenges in the implementation of the Minister of Trade Regulation Number 51/M-DAG/PER/7/2015 in the context of the local economy. The research method used was a qualitative approach by conducting in-depth interviews with traders, suppliers, and government officials. The results show that the practice of selling used clothing continues due to high consumer demand for affordable and quality products. There is a gap between policy and reality on the ground, where traders continue to sell used clothing to meet market needs. Thus, there is a need for dialog between the government and business actors to formulate policies that are more inclusive and responsive to the needs of local market consumers, especially in Pontianak City.